IDDF2020-ABS-0183 PROFILE trial: predicting outcomes for Crohn's disease using a molecular biomarker. (18th November 2020) - Noor, Nurulamin; Brezina, Biljana; Negro, Juan De La Revilla; Dowling, Francis; O'Brien, Leisha; Choudhury, Sanjana; Bond, Simon; Whitehead, Lynne; Upponi, Sara; Patel, Kamal; Seward, Abigail; Probert, Christopher; et al.
Abstract : Background: The course of IBD varies substantially between individuals, but there are a lack of reliable prognostic markers to guide clinical practice. Previously, we have described a transcriptional signature detectable within peripheral blood CD8 T-cells at diagnosis, identifying two subgroups of patients, correlating with subsequent disease course. We have sought to develop a whole-blood biomarker that could re-capitulate the prognostic CD8 subgroups and then assess whether this biomarker can improve clinical outcomes by appropriately matching therapy to disease course. Methods: From a training cohort of 69 newly-diagnosed IBD patients, we simultaneously obtained a whole-blood PAXgene RNA tube and peripheral blood CD8 T-cell sample. Gene expression in both samples was measured by microarray. Statistical modelling was used to identify a transcriptional classifier in whole-blood gene expression data re-capitulating the CD8 findings and subsequently optimised into a multi-gene qPCR assay with independent validation in a second, independent cohort of 123 newly-diagnosed adult patients. The PROFILE trial has incorporated this classifier to compare the relative efficacy of 'top-down' and 'accelerated step-up' therapy between biomarker-defined subgroups of 400 patients with newly-diagnosed Crohn's disease. Results: Following application of statistical (machine) learning methods described, a 17 gene qPCR assay was developed and optimised. The validation cohort of 123 patients, could be classified into two distinct subgroups, IBD hi (high risk) and IBD lo (lower risk). Irrespective of the underlying diagnosis, IBD hi patients experienced significantly more aggressive disease than IBD lo patients, with an earlier need for treatment escalation (hazard ratio=2.65 (CD), 3.12 (UC)). Subsequently, this biomarker is being used to stratify therapy in the PROFILE trial, where 45 sites have been opened and at the time of writing, over 260 participants randomised - with recruitment ongoing. Conclusions: We have developed, optimised and validated a whole-blood qPCR classifier that is able to predict disease course from diagnosis in patients with IBD. This classifier is currently being used in the PROFILE trial, the first biomarker-stratified trial in Gastroenterology, and if the clinical utility of a stratified treatment approach is demonstrated this would represent a major step towards personalised therapy in IBD.